Pivotal roles of phyllosphere microorganisms at the interface between plant functioning and atmospheric trace gas dynamics - Bringel, Françoise; Couée, Ivan (Frontiers in Microbiology, 2015)
The phyllosphere, which lato sensu consists in the aerial parts of plants, and therefore primarily, in the set of photosynthetic leaves, is one of the most prevalent microbial habitats on Earth. Phyllospheric microbiota are related to original and specific processes that govern the interface between plants, microorganisms and the atmosphere. Recent –omics studies have opened fascinating opportunities for characterising the spatio-temporal structure of phyllosphere microbial communities in relation with structural, functional and ecological properties of host plants, and with physico-chemical properties of the environment, such as climate dynamics and trace gas composition of the surrounding atmosphere. This review will analyse recent advances, especially those resulting from environmental genomics, and how this novel knowledge has revealed the extent of the ecosystemic impact of the phyllosphere at the interface between plants and atmosphere. Highlights • The phyllosphere is one of the most prevalent microbial habitats on Earth • Phyllospheric microbiota colonize extreme, stressful and changing environments • Plants, phyllospheric microbiota and the atmosphere present a dynamic continuum • Phyllospheric microbiota interact with the dynamics of volatile organic compounds and atmospheric trace gases